Effect of Repeated Remote Ischemic Preconditioning on Peripheral Arterial Disease in Patients Suffering from Intermittent Claudication. (10th December 2019) - Balin, Mehmet; Kıvrak, Tarık
Abstract : Background/Objective. Intermittent claudication (IC) is the symptom of peripheral artery disease (PAD) and causes functional disability. Remote ischemic preconditioning (RIPC), is a phenomenon in which a short period of sub-critical ischemia, protects tissues against ischemia/reperfusion/injury. We considered to test the hypothesis that RIPC in PAD patients suffering from IC would increase muscle resistance to ischemia and thus improve walking-capacity. Materials/Methods. A total of 63 patients with proven-IC underwent two treadmill tests (graded treadmill protocol) with a 28-day interval in between. Patients were consecutively assigned for the non/RIPC-group and RIPC-group procedure one by one. Patients received 5-cycles of alternating 5-minute inflation and 5-minute deflation of blood-pressure cuffs on nondominant upper-limb every day for four weeks. Initial claudication distance (ICD), total walking distance (TWD) and time to relief of claudication (TRC) were recorded during procedure. Results . Patients receiving-RIPC exhibited a marked increase in ICD and TWD between basal and last tests: 209.1 ± 15.4 m vs. 226 ± 15.0 m and 368.8 ± 21.0 m vs. 394 ± 19.9 m, respectively (p < 0.001 ). In addition, patients receiving-RIPC represented a significant decrease in TRC between basal and last tests: 7.8 ± 1.3 min vs. 6.4 ± 1.1 min, respectively (p < 0.001 ). Patients not receiving-RIPC did not exhibit improvement in ICD, TWD, and TRC between basal and last tests: 205.2 ± 12.1 min vs. 207.4 ± 9.9 min, 366.5 ± 24.2 min vs. 369.4 ± 23.2 min and 7.9 ± 1.4 min vs. 7.7 ± 1.3 min, respectively (p > 0.05 ). Conclusion. A significant increase in ICD and TWD were observed in last/treadmill test in RIPC-group. In addition, a significant decrease in TRC was observed in last/treadmill test in RIPC-group. In non/RIPC-group, no improvement was observed in ICD, TWD and TRC.